Associated factors for the development enamel defects in deciduous dentition, in Luis Heysen Inchaustegui Hospital, Chiclayo, 2019 - Serrano Arrasco, Karen Lizeth (2020)
Objective: To identify the factors associated with the presence of enamel development defects (DDE) of deciduous teeth. Material and methods: This was a descriptive, prospective, transversal, observational study. The sample included 135 children, 37 of whom met the inclusion and exclusion criteria of the study and all were evaluated in a dental office. Results: Descriptive statistical analysis of the data was performed with the chi-square test, contingency coefficients and gamma statistics to determine and evaluate the relationships with respect to DDE. 59% of the children evaluated were male while 41% were females, with all showing diffuse opacity. Preterm birth occurred in 30% of the cases studied, while 70% had been delivered at term. Of the children with DDE, 27% were underweight at birth. Four children with hypoplasia had had a normal weight at birth (>2500 grams), while only 10 children had a low weight (1500-2500 g), and most presented diffuse opacity. 78% of children had DDE in the previous teething area. Conclusion: The factors associated with the occurrence of DDE in this study were not related to any of the factors cited; however sex, birth weight, type of delivery, maternal infections during pregnancy and infections during the first year of the baby’s life may influence the presence of DDE.